A modalidade no discurso de professores de ensino de jovens e adultos sobre a experiência da aprendizagem mediada de Feuerstein - Oliveira, Regina Maria Loreto de (2006)
According to the educators Freire (1976, 1983, 1986, 2002, 2004) and Gadotti (2003),Youth and Adults Education (EJA henceforth, referring to Educação de Jovens e Adultos in Portuguese) allows pupils to comprehend their own language and to have access to the means of cultural production, prioritizing a dialogic relation between the students and the teacher, who plays, according to the psychologist Vygotsky (1984, 1993, 1994, 1999) and a Brazilian researcher of his studies, Kohl (1992, 1995, 2004), the mediator role, in such a way the learner becomes independent and autonomous. This study aims at assessing, through questionnaires answered by twelve EJA English language teachers, six of them working at public school and the others at private school in Sao Paulo, not only what their perceptions about mediation and teacher-mediator are, but also verifying how an authoritarian and non-dialogical conception still prevails in the teachers discourse. This questionnaire is a translation into Portuguese of twelve questions elaborated by Feuerstein (1980, 2002), who is a psychologist as well, each one associated with one parameter of mediation considered by the alluded theorist and studied by the Brazilian followers Martins de Souza et al. (2003). The teachers answers were investigated under the perspective of Halliday s (1985/1994) systemic- functional grammar, focusing on Modalization, internally realized by the Modal Operator and the Mood Adjunct expressed through causality and externally realized by adding a pseudo-sentence, the Grammatical Metaphor, which may be phrased subjectively and objectively. The recurrent utilization of must, have to, need and can in the answers denotes that the teachers are not acquainted with mediation in the scope of EJA